Family Environment Effects on Students’ Self-Efficacy and Entrepreneurial Spirit in Vocational Education - Nurfauziah (Fakultas Teknik, Universitas Negeri Makassar, 2025)
This study examines the influence of the family environment on the self-efficacy and entrepreneurial spirit of students at SMK Telkom Makassar. The research is motivated by the low entrepreneurial participation rate among vocational graduates in Indonesia, which indicates the need to identify external and psychological factors influencing entrepreneurial readiness. A quantitative ex post facto design was employed involving 96 students of the Computer and Network Engineering program. Data were collected through a Likert-scale questionnaire and analysed using descriptive statistics and simple linear regression after meeting the classical assumption criteria. The results show that the family environment has a positive and significant effect on students’ self-efficacy (b = 0.490, Sig. = 0.000) and entrepreneurial spirit (b = 0.696, Sig. = 0.000). These findings indicate that parental support, modelling, and exposure to entrepreneurial activities strengthen students’ psychological readiness to engage in entrepreneurial activities. The study concludes that the family environment serves as a key external factor shaping vocational students' entrepreneurial character and self-confidence. Further research is recommended to include additional variables and broader school contexts.